2012
DOI: 10.1037/a0026935
|View full text |Cite
|
Sign up to set email alerts
|

Lexical and sublexical semantic preview benefits in Chinese reading.

Abstract: Semantic processing from parafoveal words is an elusive phenomenon in alphabetic languages, but it has been demonstrated only for a restricted set of noncompound Chinese characters. Using the gaze-contingent boundary paradigm, this experiment examined whether parafoveal lexical and sublexical semantic information was extracted from compound preview characters. Results generalized parafoveal semantic processing to this representative set of Chinese characters and extended the parafoveal processing to radical (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
90
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(100 citation statements)
references
References 45 publications
8
90
2
Order By: Relevance
“…However, most reading studies on English have not revealed evidence of semantic information being processed parafoveally (Altarriba, Kambe, Pollatsek, & Rayner, 2001;Rayner, Balota, & Pollatsek, 1986;Rayner, Schotter, & Drieghe, 2014). In contrast, the semantic preview effect is quite robust and has been found in a number of studies on Chinese (Yan, Richter, Shu, & Kliegl, 2009;Yan, Zhou, Shu, & Kliegl, 2012). These results suggest that semantic processing may occur differently during Chinese reading and the reading of alphabetic languages, and it is very likely that Chinese readers can perceive semantic information more easily because they receive more information through parafoveal vision during sentence reading.…”
Section: Discussionmentioning
confidence: 52%
“…However, most reading studies on English have not revealed evidence of semantic information being processed parafoveally (Altarriba, Kambe, Pollatsek, & Rayner, 2001;Rayner, Balota, & Pollatsek, 1986;Rayner, Schotter, & Drieghe, 2014). In contrast, the semantic preview effect is quite robust and has been found in a number of studies on Chinese (Yan, Richter, Shu, & Kliegl, 2009;Yan, Zhou, Shu, & Kliegl, 2012). These results suggest that semantic processing may occur differently during Chinese reading and the reading of alphabetic languages, and it is very likely that Chinese readers can perceive semantic information more easily because they receive more information through parafoveal vision during sentence reading.…”
Section: Discussionmentioning
confidence: 52%
“…Chen and Allport (1995) were the first to demonstrate that semantic radicals only influence participants' performance in semantic comparison task, and that phonetic radicals only influence participants' performance in phonological comparison task. Numerous studies have separately investigated the functional roles of semantic radicals (Chen & Weekes, 2004;Feldman & Siok, 1999a, 1999bLeck et al, 1995;Yan, Zhou, Shu, & Kliegl, 2012) and phonetic radicals (Flores d' Arcais et al, 1995;Hue, 1992;Lee et al, 2004Lee et al, , 2007Liu et al, 1996Liu et al, , 2003Saito et al, 1998;Seidenberg, 1985;Tzeng, Lin, Hung, & Lee, 1995;Zhou & Marslen-Wilson, 1999). Until now, there seems to be no consensus about how the function of the radicals is implemented in Chinese character processing.…”
Section: Discussionmentioning
confidence: 95%
“…14! identification and reading (Wang et al, 2013;Yan et al, 2012). In stark contrast to Chinese, because Finnish and English are alphabetic, the written form is horizontally spatially extended to a greater degree, with the constituent letters of words being presented horizontally adjacent to each other.…”
Section: ! 8!mentioning
confidence: 99%